Diseño De Tratamiento De Agua Residual Para La Quebrada Yayata, En El Municipio De Silvania, Colombia (2023)
The project consists of the design of a wastewater treatment system in the Yayata tributary, where the community mentions the rural areas of the municipality of Silvania, Colombia. A main factor would be the wastewater discharges and for this purpose an investigation of a wastewater treatment system was carried out in order to design an appropriate method in relation to the problems of the creek, a comparative was made in treatment processes evidencing the differences, components, qualities, disadvantages and costs, as the study area where the design will be implemented. According to the above, the elaboration of an A.A.F.F.F. (Anaerobic Upflow Filter) was determined as a working methodology.